Sound Diversity as Representation to the Behavior of Spiny Lobster Panulirus homarus (Linnaeus, 1758) - Hartoyo Hartoyo; Amron Amron; Aristi Dian Purnama Fitri; YS Darmanto (Jurnal Ilmiah Perikanan dan Kelautan, 2022)
Highlight Research The sound of d spiny  lobster (Panulirus homarus) was identified, named rasp; slow rattle; and popping sound The sound characteristics of  spiny  lobster (Panulirus homarus) represent its behavior Passive acoustic and visual record method combination was implemented to analyze the relation between sounds and behavior of  spiny  lobster (Panulirus homarus)   Abstract Spiny lobster Panulirus homarus is one of many important economic fishery resources in Indonesia. Continuous exploitation activities in the natural habitat can potentially disturb the sustainability of lobster resources. This species is known to produce sound with certain characteristics and highly dependent on environmental changes. This study aimed to investigate the characteristics of sound as a representation of behaviour. The sound produced by P. homarus was recorded for 24 hours using a hydrophone (a passive acoustic technique). The hydrophone converts the sound wave produced by the lobsters into electric voltage in millivolts, then were converted to a digital number, in order to be saved in a virtual format with the *.wav extension. The video system captured data on behaviors of resting, territoriality, aggression, and social attitudes. The results showed that P. homarus emitted rasp, slow rattle, and popping type of sound, with certain characteristics. All sounds types were characterized by a broadband frequency (4 - 20 kHz), and a source level ranging from 125 - 145 dB re 1 µPa. Rasp sound consisting of 12 - 40 pulses with a sound duration of 100 - 400 ms, represents a defensive behavior. Slow rattle sound with 2 - 7 pulses did not represent a specific behaviour and it is dominant during the night. However, the popping sound with only one pulse represented feeding behavior.